Synthesis of Green Diesel from Non-edible Kapok (Ceiba petandra) Seed Oil via Hydrotreating Process Using Sulfided Ni-Mo/Al2O3 Catalysts - Hudaya, Tedi; Rahardja, Sarah Amadea; Gunawan, Michael; Soerawidjaja, Tatang Hernas (ASEAN Journal of Chemical Engineering, 2024)
The demand for environmentally friendly and renewable fuels will keep increasing due to the accelerated climate change worldwide. Ceiba pentandra seed oil is a promising feedstock for renewable fuel since it possesses major fatty acid components with similar skeletal structure to diesel-range hydrocarbons. Nevertheless, its direct utilization will potentially cause problems due to the cyclopropenoid group and its high viscosity. In this research, hydrotreating processes over bimetallic sulfided Ni-Mo/g-Al2O3 catalysts were performed to convert the kapok seed oil into green diesel, with lower cloud points compared to those derived from other common vegetable oils. The hydrotreating process was needed not only to eliminate cyclopropenoid and oxygen contents but also to reduce the unsaturated bonds and, at the same time, increase its H/C ratio. The BET measurement showed the catalyst surface area of 144 m2/g, while the existence of NiS and MoS2 as active sites on its surface was detected by XRD analysis. The TEM analysis indicated that sulfided Ni and Mo were dispersed reasonably well, with a little aggregation, on the catalyst surface. The most well-performed catalyst (with Ni:Mo ratio of 0.2:1 and K:P promoter ratio 0.5:1) successfully synthesized bio-hydrocarbons (with desirable C15-C19 diesel range) with the conversion of almost 96%, with no remaining cyclopropenoid content.